Teacher' and Student's Perspective on the Use of Mall (Mobile -Assisted Language Learning) in English Learning - Okny Apriani S; Widi Syahtia Pane; Godefridus Bali Geroda (Wadah Inovasi Indonesia, 2023)
Mobile-Assisted Language Learning (MALL) is a new approach to language learning and teaching activities that can improve effectiveness, flexibility, and comfort in language learning by allowing the sending and receiving of learning materials, information, and instructions via mobile phone. The objectives of the researchers are to find out the teacher and students' perspectives toward the use of MALL (Mobile Assisted Language Learning) in English learning at SMK Negeri 5 Samarinda. In this research, the researcher used qualitative research and a phenomenology approach. This research was conducted at SMK Negeri 5 Samarinda in class XII multimedia. With a purposive sampling method, the researcher chose 20 students and 1 English teacher. Collecting data in this study used interview techniques to find out the perspectives of teachers and students on the use of MALL in English learning activities. The results of the study showed a positive response from the perspectives expressed by teachers and students towards the use of MALL in learning English, where students felt that the MALL helped and made it easier for them to learn English. Furthermore, the teacher said that the existence of a mall helps teachers provide more varied learning